2021
DOI: 10.4103/jhrs.jhrs_190_20
|View full text |Cite
|
Sign up to set email alerts
|

Observable Protective Activities of Quercetin on Aluminum Chloride-Induced Testicular Toxicity in Adult Male Wistar Rat

Abstract: Background: Aluminum chloride (AlCl3 ) present in many manufactured consumable is considered as a toxic element. Aim: Our study evaluates the toxic effects induced by AlCl3 on the testes as well as the therapeutic tendency of Quercetin (QUE) agent as an antioxidant. Setting and Design: In the department of Anatomy of Medical School. Methods and Materials: Thirty-two male Wistar rats weighing approximately 170 ± 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Anticancer drugs, including cyclophosphamide, methotrexate, tamoxifen, doxorubicin, and 5-fluorouracil administration, have been associated with the induction of oxidative stress and inflammation [ 57 ]. Such results, confirmed by another flavonoid (quercetin), [ 54 ] found that coadministration of quercetin to the aluminum chloride-treated group decreased the iNOS expression in testis tissue. HSP caused a marked decrease in the CP-induced expression of iNOS in the liver [ 58 ] and renal tissue [ 59 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Anticancer drugs, including cyclophosphamide, methotrexate, tamoxifen, doxorubicin, and 5-fluorouracil administration, have been associated with the induction of oxidative stress and inflammation [ 57 ]. Such results, confirmed by another flavonoid (quercetin), [ 54 ] found that coadministration of quercetin to the aluminum chloride-treated group decreased the iNOS expression in testis tissue. HSP caused a marked decrease in the CP-induced expression of iNOS in the liver [ 58 ] and renal tissue [ 59 ].…”
Section: Discussionmentioning
confidence: 62%
“…The CP-treated group revealed a significant increase in iNOS, only formed during inflammation, ischemia, and apoptosis [ 51 ], immune reactivity in the cytoplasm of the cells of the seminiferous tubules [ 52 ]. Exposure to cisplatin, aluminum chloride, methotrexate, and silica nanoparticles reported an increase in testicular iNOS expression [ 53 , 54 , 55 , 56 ]. Anticancer drugs, including cyclophosphamide, methotrexate, tamoxifen, doxorubicin, and 5-fluorouracil administration, have been associated with the induction of oxidative stress and inflammation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the oxidative injury was significantly recovered, and the antioxidant biomarkers such as GSH levels, SOD, and CAT activities were close to normal with co-administration of QCN, and the toxic symptoms following exposure to Al 2 O 3 NPs in mice were avoided (Shrivastava et al 2014 ). Quercetin improved the oligospermia, male sex hormonal effects, and functional deficit induced by aluminum chloride and significantly reduced the degenerative testicular changes in Wistar rats (Olanrewaju et al 2021 ). Thus, the current study demonstrates the hazardous effects of Al 2 O 3 NPs + Pb co-exposure along with their independent exposure and the role of QCN against that co-exposure in male rats.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum is found in airborne dust particles, food additives, phosphate binders, antacids, buffered analgesics, antiperspirants, cooking vessels, tinned boxes, infant formulas, cosmetics, mining, drinking water, and several herbal preparations [1,3]. For example, aluminum chloride (AlCl 3 ) is present in many manufactured consumables and is considered a toxic element [4]. Heavy metals are regarded as harmful compounds that pose health risks to humans and animals, as frequent ingestion of small amounts of these metals causes their progressive and irreversible accumulation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of aluminum-containing items raises the concentration of this metallic element in consumers' organs, resulting in testicular tissue injuries. Aluminum chloride has been shown to cause testicular toxicity in adult male Wistar rats [4] and cause male reproductive impairment in rats [16] . Aluminum has also been linked to testicular damage caused by increased nitric oxide (NO) levels [17].…”
Section: Introductionmentioning
confidence: 99%